Financial Distress, Regional Independence and Corruption: An Empirical Study in Indonesian Local Governments - Evi Maria; Abdul Halim; Eko Suwardi (Journal of Accounting and Strategic Finance, 2021)
This study aims to determine the effect of financial distress and regional independence on the probability of corruption in the local governments, Indonesia. This study used panel data of local governments in Indonesia in 2012 and 2013 with a total of 785 local governments. Data were analyzed using logistic regression analysis. The study results found that financial distress had no effect on the probability of corruption, while regional independence had a positive effect on the probability of corruption in the local governments, Indonesia. This means that if the regional independence is high then the probability of corruption in the local government is also high, vice versa. The study findings were also robust in a separated analysis, when additional test was carried out. This study found empirical evidence that the independence of funding sources, independence ratios to meet regional needs, and the amount of regional income could be used to detect corruption in local governments, Indonesia, while the budget solvency ratio, financial performance ratio of budget, financial performance ratio of fund equity and regional financial efficiency could not.